THE INFLUENCE OF CUSTOMER VALUE, SERVICE QUALITY AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION IN THE PACARKEMBANG VILLAGE - Riyanti Sumee; Yessy Artanti; Sanaji Sanaji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the influence of customer value, service quality, and customer experience on customer satisfaction in Pacarkembang Village. This study uses an explanatory survey method, with a purposive sampling technique using 100 respondents. The analysis technique used is multiple linear regression analysis with SPSS 23 software. The results of this study indicate that there is an influence between customer value and customer satisfaction. Service quality has a significant positive influence on service satisfaction. However, customer experience does not affect customer satisfaction